Open Access publishing and academics’ career assessment. Peer reviewers knowledge and opinions regarding open access journals in Argentina, Brasil and Mexico - Bongiovani, Paola Carolina; Gomez, Nancy Diana; Costa, Sely Maria de Souza; Rodríguez Jiménez, Teresa Margarita; Leite, Fernando César Lima; De Volder, Carolina; Moscoloni, Nora (Public Knowledge Project (PKP) Scholarly Publishing Conference 2013, 2013)
This presentation will discuss the project “Open Access (OA) and Academic Assessment. Researchers who serve in academic assessment committees’ knowledge and opinions regarding open access publishing in Argentina, Brazil and México” within the major project Quality of Open Access Publishing in Latin America. The work reported surveys the knowledge, attitudes and opinions regarding OA publishing among researchers who evaluate the academic career of their peers in the area of Social Sciences in Argentina, Brazil and Mexico. A literature review identified that peer review, the prestige of journals and the need to reach their target audiences are the main motivations of researchers to choose where to publish their work, regardless of journals’ economic model (Cooning and Younce, 2009, Harley et al, 2010). Previous studies found an increase of scholars’ awareness of open access journals (Swan and Brown, 2004; Xia, 2010), although this has not been directly translated to their publication practices. Moreover, authors did not publish in open-access journals because of at least three reasons. First, they were not familiar with OA journals. Second, they considered OA journals to have low prestige and impact in the academic community they wanted to reach. Finally, due to high publishing fees of some OA journals (Harley et al., 2007; Xia, 2010; Dallmeier-Tiessen et al., 2011; Gómez et al., 2008; Sánchez-Tarragó y Fernández-Molina; 2008; Miguel et al., 2012; Bongiovani et al., 2012). It was also found that researchers feared that their academic careers could be negatively affected if they published in OA journals (Mann et al., 2009; Harley , et al., 2010; Pontika, 2011). Considering that specific research results are missing (Hurrell and Meijer-Kline, 2011) it was deemed important to study knowledge, attitudes and opinions regarding OA publishing among researchers who evaluate the academic career of their peers in Latin-America. The assumption behind the proposal is that if these researchers are not familiar with OA journals or do not value them, then peers undergoing evaluation may be unwilling to publish in OA journals, even if they considered them beneficial. Methodology: in order to collect data, an online survey will be sent to a representative sample of social science research committee members at Teaching and Research Incentive Program of National Universities in Argentina, CNPq and CAPES in Brazil, and National Researchers System of CONACYT in México. The study focus on factors influencing where authors choose to publish; relevant aspects considered in the evaluation of peer researchers; knowledge, opinions and attitudes towards OA journals; perceptions about both benefits and incentives provided by OA publications and difficulties and/or concerns about these new publications outlets. Results: Preliminary results obtained will be presented at the conference.

Esta ponencia presenta los avances del proyecto Acceso Abierto y Evaluación Académica. Conocimientos y opiniones de los evaluadores de carrera docente investigador respecto de las publicaciones de Acceso Abierto (AA) que se desarrolla en el marco del proyecto “Calidad en la Comunicación Científica de Acceso Abierto en América Latina”. En este marco se investigan los conocimientos, opiniones y actitudes respecto a la publicación en revistas de AA de investigadores miembros de comités evaluadores de carrera científico-académica de sus pares en el área temática de Ciencias Sociales en Argentina, Brasil y México. En un análisis de la literatura sobre el tema se identificó que la revisión por pares, el prestigio de las revistas y la necesidad de llegar a su audiencia de interés son las principales motivaciones de los investigadores al elegir dónde publicar sus trabajos, más allá de que las publicaciones sean AA o por suscripción (Cooning y Younce, 2009; Harley y otros, 2010). Se observó un creciente conocimiento de los investigadores respecto a las revistas de AA (Swan y Brown, 2004; Xia, 2010), sin embargo esto no se ha trasladado directamente a sus prácticas de publicación. Entre las razones de los investigadores para no publicar en AA surgen el desconocimiento, el bajo prestigio e impacto de estas revistas en la comunidad académica a la que quieren llegar y los costos de publicación en algunas revistas AA (Harley y otros, 2007; Xia, 2010; Dallmeier-Tiessen y otros, 2011; Gómez y otros, 2008; Sánchez-Tarragó y Fernández-Molina; 2008; Miguel y otros, 2012; Bongiovani y otros, 2012). Adicionalmente se encontró que los investigadores temían que sus carreras académicas podrían ser afectadas negativamente al publicar en revistas AA (Mann y otros, 2009; Harley y otros, 2010; Pontika, 2011). De acuerdo a los antecedentes citados, y dado que no se han encontrado resultados de estudios específicos (Hurrell y Meijer-Kline, 2011) se consideró necesario estudiar las opiniones y conocimientos sobre el AA de aquellos investigadores que integran comités de evaluación de las carreras de sus pares en A.L Si quienes evalúan a sus pares desconocen o no valoran positivamente las revistas de AA, por tanto se presupone que los investigadores sometidos a evaluación serán renuentes a publicar en éstas, por más que las conozcan y consideren beneficiosas. Metodología: Se aplicará una encuesta online dirigida a una muestra representativa de investigadores en Ciencias Sociales miembros de comités evaluadores del Programa de Incentivos a Docentes Investigadores de las Universidades Nacionales de Argentina, del Consejo Nacional para el Desarrollo Científico y Tecnológico y CAPES de Brasil y del Sistema Nacional de Investigadores del CONACYT de México. Se indagan: factores que influyen en la elección de las revistas donde publican; aspectos relevantes considerados en la evaluación de la producción científica de sus pares; conocimientos, opiniones y actitudes respecto de las revistas de AA; percepciones tanto respecto de los beneficios e incentivos más importantes de las publicaciones de AA como de las dificultades y/o preocupaciones que les generan estas publicaciones. Resultados: Se presentan los resultados preliminares obtenidos.
Conocimientos y opiniones de los evaluadores de carrera docente investigador respecto de las publicaciones de Acceso Abierto en Argentina, Brasil y México
Keywords: Acceso Abierto; Evaluación Académica; Publicaciones; Evaluadores de carrera docente investigador; Revistas; Conocimientos, opiniones y actitudes; Ciencias Sociales; Argentina; Brasil; México; Open Access; Career assessment; OA journals; Knowledge, attitudes and opinions; Researchers; Academics